Prevalence of inadequate vitamin D status in ambulatory Thai patients with cardiometabolic disorders who had and had no vitamin D supplementation - Nipith Charoenngam (2019)
© 2018, Medical Association of Thailand. All rights reserved. Background: Data regarding the prevalence of inadequate vitamin D status in ambulatory Thai population with cardiometabolic disorders (CMDs) are scarce. Objective: To investigate the prevalence of hypovitaminosis D in ambulatory Thai patients with CMDs with and without vitamin D supplementation (DS). Materials and Methods: This descriptive cross-sectional study randomly recruited patients with one or more CMDs that attended the outpatient clinic during December 2016 to May 2017. CMDs included type 2 diabetes (T2DM), hypertension (HT), dyslipidemia (DLP), and coronary artery disease (CAD). Serum 25-hydroxyvitamin D (25-OHD) levels were measured by electrochemiluminescence immunoassay. Results: Four hundred and forty-four patients were included. Mean age was 65.79±10.12 years, 72.3% were aged >60 years, and 35.1% were male. CMDs included T2DM (75.9%), prediabetes (11.7%), HT (72.1%), DLP (88.3%), and CAD (7.4%). Mean serum 25-OHD was 26.12±10.10 ng/mL, with 29.7%, 42.1%, 25.5%, and 2.7% of patients having serum 25-OHD level of ≥30, 20-<30, 10-19.9, and <10 ng/mL, respectively. Twenty percent of patients had DS. Prevalence of 25-OHD <20 ng/mL and <30 ng/mL were lower in patients with DS than in patients without DS (19.1% vs. 30.6% and 61.7% vs. 72.6%, respectively, both p <0.05). Among the 350 patients without DS, prevalence of 25-OHD <10 ng/mL was higher in patients with HT and patients with CAD than in those without (3.9% vs. 0.0% and 14.8% vs. 1.9%, respectively, both p<0.05). Male patients had higher serum 25-OHD levels and lower prevalence of 25-OHD <30 ng/mL and 25-OHD <20 ng/mL than did the female patients (29.10±11.61 vs. 23.76±8.69 ng/ mL, 57.4% vs. 81.4%, and 20.9% vs. 36.2%, respectively, all p <0.005). Non-elderly patients (age ≤60) had lower serum 25-OHD levels and higher prevalence of 25-OHD <30 ng/mL and 25-OHD <20 ng/mL than did the elderly patients (age >60) (23.23±9.20 vs. 26.81±10.41 ng/mL, 82.1% vs. 68.4%, and 43.4% vs. 25.0%, respectively, all p<0.01). Conclusion: Prevalence of inadequate vitamin D status in ambulatory Thai patients with one or more CMDs was high in patients with and without DS. It was higher in patients without DS than in both patients with DS and all patients regardless of DS status. Factors associated with higher prevalence of inadequate vitamin D status in patients with CMDs included HT, CAD, age ≤60 years, and female gender.